Drivers of Health Insurance Coverage in Low Income Settlements: A Case of Kibera Informal Settlement, Nairobi County, Kenya - Emmah Wanjiku Ng’ang’a; Martine Oleche Odhiambo (European Scientific Journal, ESJ, 2023)
Insurance is critical for any country's economic growth and development to be sustainable. In rural areas of Kenya, among the illiterate, unemployed, poor, and vulnerable in society, health insurance adoption is extremely low. The purpose of this study was to determine the factors that influence health insurance uptake among low-income populations in Kibera, Nairobi County. Data was collected through semi structured questionnaires administered to households located in Kibera. Simple random sampling was adopted in selecting 399 respondents. In estimation, the study employed binary Probit regression model where health insurance ownership was used as the dependent variable while age, gender, marital status, household size, school attainment, occupation, income levels, religion, cultural beliefs, frequency of hospital visits, cost of premiums and also pre-existing illness were used as the independent variables. Results showed that only 27.6 percent of the respondents had health insurance coverage. Following model estimation, the findings revealed that occupation, income levels, and religion significantly influence health insurance ownership among low-income populations in Kibera, Nairobi. Public health insurance cover was the most owned type of health insurance scheme. Recommendations were for the ministry of health and other relevant stakeholders to raise knowledge on the various health insurance options available and improve flexibility of the products in order to drive insurance uptake. In addition, national and county governments need to develop programmes and policies that could empower households in the informal settlements. Further, it is necessary for the government to subsidize the cost of acquiring public health insurance covers since this would encourage uptake among low-income families. Lastly, the ministry of health should work in conjunction with various religious denominations to campaign for uptake of health insurance among the poor.